EU employment and social situation Quarterly Review indicates little improvement despite first signs of recovery - European Commission Directorate-General for Employment, Social Affairs and Equal Opportunities (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2014)
The recent economic recovery has not yet been able to create new jobs and the social situation in the EU shows little signs of improvement so far, according to the European Commission's latest Employment and Social Situation Quarterly Review. This analysis also points to an expected increase in poverty levels and a slight improvement in the effectiveness of social protection expenditure in 2013, even if its impact remains very weak. The Review provides empirical evidence that the crisis at its height had the strongest adverse impact on the employment situation of men and young people. The latest Quarterly Review stresses that the improvements in the EU labour markets are still weak. Employment showed the first signs of stabilisation in 2013, with a 0.1% growth in the second half of the year.
Related Documents : 1. EU Employment and Social Situation - Quarterly Review - March 2014. 2. EU Employment and Social Situation - Quarterly Review - March 2014 - Supplement on labour market transitions. 3. EU Employment and Social Situation - Quarterly Review - March 2014 - Supplement on trends in poverty and social exclusion. 4. EU Employment and Social Situation - Quarterly Review - March 2014 - Supplement on trends in social expenditure. 5. 10 key facts and figures: EU Employment and Social Situation - Quarterly Review - March 2014.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Labour market; Social situation; Unemployment -- European Union countries; Labor policy -- European Union countries; European Union countries -- Social policy; Electronic books